Ecological security of economic belt from the symbiosis perspective--a case study of the Yangtze river economic belt. Issue 1 (September 2020) - Wu, Yanxia; Wang, Yajuan; Wang, Yanlong
Abstract: As an advanced stage of the urbanization process and the main force driving the high-quality development of China's economy, the economic belt has caused the emergence of ecological security problems in the economic belt while its economic growth. In this paper, the Yangtze River Economic Belt, a national strategic layout area, is used as an empirical research. Based on the symbiosis theory, the Lotka-Volterra model for ecological security measurement of symbiotic development is constructed, and according to the actual conditions of 11 provinces and cities in the Yangtze River Economic belt, comprehensive evaluation of the ecological security of its are conducted. The research results show that: (1) From 2008 to 2017, the overall ecological carrying capacity of the Yangtze River Economic Belt was low, and the regional ecological conditions have improved but not obvious; (2) Through the reverse decoupling of indicators, it was found that the resources along the Yangtze River were over-exploitation, the serious pollution of industries and agriculture, and the base of pollutant emissions is large; (3) To improve the resources and ecological environment of the Yangtze River Economic Belt, it is necessary to strengthen source prevention, comprehensively promote pollution remediation, repair damaged ecology, and promote green sustainability development.